PENGEMBANGAN KOMIK DAN LEMBAR KERJA SISWA DENGAN PENDEKATAN MATEMATIKA REALISTIK UNTUK MENINGKATKAN HASIL BELAJAR DI SD NEGERI 060843 - Arfiliana Arfiliana; Waminton Rajagukguk; Edy Surya (JURNAL TEMATIK, 2018)
The objective of this study is to developing teaching materials of comic form and student worksheets of flat-shape structure material for third grade students of elementary school 060843 with Realistic Mathematics Education. This research is a Research & Development (R & D), Van den Akker models (1999). The samples in this study were 40 third-grade students, for every I and II trials. The result of this study showing  that comics, student’s worksheet, and the learning outcomes tests was valid and excellent. The improvement of learning outcomes of students occurred very well.  The mean score result on first initial trial test before using the developed teaching materials was 64,25, and then on the final test after using the developed teaching   material the mean score was 87,88. On the second trial test, the mean score on the initial test was 64,13, while on the final test the mean score was 88,38. Based on the observation of teacher’s activities, students, teacher’s impressions , student’s responses, and the student’s  teaching outcomes that including completeness of objective and classical, then the implementation of comics and student’s worksheet with Realistic Mathematics Education could be declared effective and excellent.